The limit solubility relationships based on Frenkel’s heterophase fluctuations theory - Shapovalov, R.V.; Osmayev, O.A. (Вопросы атомной науки и техники, 2012)
For a weak one-component solution, in which the solvent and dissolved substances are not chemically bound, a simple analytical approximation was found for temperature dependence of limiting solubility of the dissolve substance. The derivation of the approximation is based on the Frenkel theory of heterophase fluctuations. It was shown how the parameters of this analytical approximation can be related to experimental data. Для слабого однокомпонентного раствора, в котором растворитель и примесь не образуют химического соединения, получено аналитическое приближение, позволяющее найти предельное количество растворенного вещества в зависимости от температуры. Вывод приближения основан на теории гетерофазных флуктуаций Френкеля. Показано, как параметры аналитического выражения могут быть связаны с экспериментальными данными. Для слабкого однокомпонентного розчину, у якому розчинник та домішка не створюють хімічної сполуки, отримано аналітичне наближення, яке дозволяє знайти граничну кількість розчиненої речовини в залежності від температури. Наближення знайдено на базі теорії гетерофазних флуктуацій Френкєля. Показано, як параметри аналітичного співвідношення можуть бути пов’язані з даними експериментів.